Impact The Covid 19 Pandemic on the Tourism Business Stakeholders Performance in Bogor City - Marpaung, Annaria Magdalena; Hadi, Cecilia Valentina Sri; Marpaung, Bintang Sahala (Jurnal Ilmiah Manajemen Kesatuan, 2024)
Pandemic and Tourism Business Performance _____1147 Submitted: MAY 2024 Accepted: JULY 2024 This study done with objective For know How impact covid 19 pandemic against performance of the perpetrators business restaurants and hotels . Deep sample this study are the perpetrators business restaurant and hotel located in the city of Bogor . Data collection was carried out with do interview direct with perpetrator business . Research result show application Policy Health Protocols in sectors tourist give impact positive form obedience public . Ownership CHSE certificate , provide impact positive on the entity industry supporter tourist Hotel and Destination category Tourism , and not give influence significant in the Restaurant category Keywords: Covid 19 pandemic , activities business , CHSE.